Production and reproduction performance of light breed of buffaloes - BHARAT, N K; THAPAN, P C; GAHLOT, G C (The Indian Journal of Animal Sciences, 2014)
The perfonnance of light breed of buffaloes (Surti and Mehsana) was evaluated in terms of production and reproduction parameters from the data collected from 2 farms, Dharwar, University of Agricultural Sciences, Bangalore and Vallabhnagar, Sukhadia University, Udaipur. About 2 534 lactations of 898 Surti, Mehsana and crossbred buffaloes from 1965 to 1984 were studied for significant effect of breed, farm, period and season of calving and lactation order. The analysis revealed that Mehsana and MehsanaxSurti butfaloes were significantly superior to Surti breed for full lactation yield, lactation yield, lactation length, while for milk yield/lactation length, milk yield/calving interval and peak yield Mehsana had higher yield than Surti and SurtixMehsana. Significant ditferences were also observed among farms, periods. seasons and parities for most of the traits. The least-squares means were 1201 .00±32.43 and 1 350.35±35.39 kg for full lactation yield, 1 350.35±35.39 and 1264.52±27. 12 kg for lactation yield, 294.44±6.66 and 309.57±7.22 days for lactation length, 4.09±0.06 and 4.37±0.07 kg for MY/LL, 2.50±0.08 and 2.71±0.08 kg for MY/Cl, 7.16±0.11 and 7.71±0.12 kg for peak yield, 3 1.28±2.06 and 34.00±2.17 days for days to attain peak, 21 5.46±13.94 and 215.46±13.94 days for dry period, 517. 12±20.44 and 521. 1 2±21.20 days for calving interval tor Surti and Mehsana buffaloes respectively.